Rapid Sequential Implication of the Human Medial Temporal Lobe in Memory Encoding and Recognition - Tautvydaitė, Domilė; Adam-Darqué, Alexandra; Manuel, Aurélie L.; Ptak, Radek; Schnider, Armin (Frontiers in Behavioral Neuroscience, 2021)
The medial-temporal lobe (MTL) is crucial for memory encoding and recognition. The time course of these processes is unknown. The present study juxtaposed encoding and recognition in a single paradigm. Twenty healthy subjects performed a continuous recognition task as brain activity was monitored with a high-density electroencephalography. The task presented New pictures thought to evoke encoding. The stimuli were then repeated up to 4 consecutive times to produce over-familiarity. These repeated stimuli served as ‘baseline’ for comparison with the other stimuli. Stimuli later reappeared after 9 to 15 intervening items, presumably associated with new encoding and recognition. Encoding-related differences in evoked response potential amplitudes and in spatiotemporal analysis were observed at 145-300 ms, whereby source estimation indicated MTL and orbitofrontal activity from 145 to 205 ms. Recognition-related activity evoked by late repetitions occurred at 405-470 ms, implicating the MTL and neocortical structures. These findings indicate that encoding of information is initiated before it is recognized. The result helps to explain modifications of memories over time, including false memories, confabulation, and consolidation.